Effect of Noni Fruit Extract (Morinda citrifolia L.) And Application Time To Control Crocidolomia binotalis Zell. On Cabbage Plant - Rahmawati, Dewi; Djamilah, Djamilah; Simanihuruk, Bilman W (Akta Agrosia, 2019)
Crocidolomia binotalis Zell is an important pest in Brassicaceae vegetable crops. Vegetable insecticide is one potential alternative to controlling the pest. This study aims to determine the application time of noni fruit extract and to determine the effective concentration of noni fruit extract as a vegetable insecticide in controlling C. binotalis larva on cabbage plants in the field. this study used a Completely Randomized Design (RAL) consisting of two treatment factors and four replications. The first factor is the concentration of extract (5 ppm, 10 ppm, 15 ppm and 20 ppm) and the second factor is the time of application of vegetable pesticide before the pest is invested (W1) and after the pest is invested (W2). So there are 32 units of experiments and 4 units of experiments added as control. The results showed, noni fruit extract had no significant effect on mortality of C. binotalis larvae. The highest mortality rate is at 100% K2 (10ppm) concentration at the time of application before the pest is invested (W1). The interaction had significant effect on the wet weight of the plant canopy but had no significant effect on the mortality of the pest, the intensity of the attack, the percentage of pupa formed, and the present percentage of imago.